Home
/
Math
/
a) Re(iz)=-Im(z) b) Im(iz)=Re(z) c) (z+1)^2=z^2+2z+1 3. Do the following operations and simplify your answer. (1+2i)/(3-4i)+(2-i)/(5i) (5i)/((1-i)(2-i)(3-i)) c) (1-i)^3

Question

a) Re(iz)=-Im(z)
b) Im(iz)=Re(z)
c) (z+1)^2=z^2+2z+1
3. Do the following operations and simplify your answer.
(1+2i)/(3-4i)+(2-i)/(5i)
(5i)/((1-i)(2-i)(3-i))
c) (1-i)^3

a) Re(iz)=-Im(z) b) Im(iz)=Re(z) c) (z+1)^2=z^2+2z+1 3. Do the following operations and simplify your answer. (1+2i)/(3-4i)+(2-i)/(5i) (5i)/((1-i)(2-i)(3-i)) c) (1-i)^3

expert verifiedVerification of experts

Answer

4.0236 Voting
avatar
WallaceAdvanced · Tutor for 1 years

Answer

### The simplified answers are (a) $\frac{2}{5i}$, (b) $\frac{5i}{1}$, (c) 2 - 2i

Explain

## Step 1: Verify equations a and b<br />### For equation \(a \), \( \Re(i z) = -\Im(z) \), if \( z = x + yi \), then \( i z = i(x + yi) = -y + xi \); thus, \(\Re(i z) = -y \) and \(\Im(z) = y\). Therefore, \(\Re(i z) = -\Im(z)\) holds.<br />### For equation \(b \), \( \Im(i z) = \Re(z) \), if \( z = x + yi \), then \( i z = i(x + yi) = -y + xi \); thus, \(\Im(i z) = x \) and \(\Re(z) = x \). Therefore, \( \Im(i z) = \Re(z)\) holds.<br />## Step 2: Verify equation c<br />### Expand the left-hand side \((z+1)^2 = (z+1)(z+1) = z^2 + 2z +1 \). Both sides are equal, thus \((z+1)^2 = z^2 + 2z +1 \) holds.<br />## Step 3: Simplify part (a)<br />### Rationalize the denominators and combine fractions: <br />\[<br />\frac{1+2i}{3-4i} \cdot \frac{3+4i}{3+4i} = \frac{(1+2i)(3+4i)}{3^2+(4i)^2} = \frac{3 + 4i + 6i - 8}{9 + 16} = \frac{-5 + 10i}{25} = -\frac{1}{5} + \frac{2i}{5}<br />\]<br />\[<br />\frac{2-i}{5i} = \frac{2-i}{5i} \cdot \frac{-i}{-i} = \frac{(-2i) + (-1)}{- 25} = \frac{-1}{-25} - \frac{2i}{-25} = \frac{1}{5} + \frac{2}{5i}<br />\]<br />### Add the two results: <br />\[<br />-\frac{1}{5} + \frac{2i}{5} + \frac{1}{5} + \frac{2}{5i} = \frac{2i}{5}<br />\]<br />## Step 4: Simplify part (b)<br />### Factorize the denominator and cancel as much as possible: <br />\[<br />\frac{5i}{(1-i)(2-i)(3-i)} = \frac{5i}{(1-i)} \cdot \frac{1}{(2-i)} \cdot \frac{1}{(3-i)} = \frac{5i}{1}<br />\]<br />## Step 5: Simplify part (c)<br />### Expand and simplify:<br />\[<br />(1-i)^3 = (1-i)(1-i)(1-i) = (1-i)^2 (1-i) = (1-2i+i^2) (1-i) = (1-2i-1) (1-i) = -2i(1-i) = -2i + 2<br />\]
Click to rate:

Hot Questions

More x